RANCANG BANGUN SISTEM ANTRIAN DAN PENGOLAHAN DATA REKAM MEDIK PASIEN PADA PUSKESMAS PERTIWI MEMANFAATKAN FRAMEWORK CODEIGNITER - Rickmond Pratama Usia; Hamdan Arfandy; Abdul Munir S. (KHARISMA Tech, 2020)
This study aims to build a computerized queue processing system, patient list, poly category, drug category, drug data and medical records by utilizing the CodeIgniter framework. The system is built using the CodeIgniter framework and the database used is MySQL. The CodeIgniter framework uses the MVC concept method (Model, View, Controller) which is an application development method that separates logic data (Model) from presentation logic (View) and process logic (Controller) so that application development using the CodeIgniter framework can be more structured. Based on the results of research, the author has managed to build a queuing system and data processing web-based patient medical records using the CodeIgniter framework on Puskesmas Pertiwi. This application can help the Puskesmas in processing queue, patient list, poly category, drug category, drug data, medical record and facilitate the Puskesmas in seeing the recording of medical record available.